Pays des brumes: The Persistence of Poetic Realism in French Cinema of the Occupation. Issue 1 (1st March 2022) - Nevin, Barry
Abstract: Whereas the aesthetics and politics of poetic realism in French prewar cinema have been analyzed in depth, the extent to which poetic realism persisted in French cinema of the Occupation and the textual space that it created for spectators within this cultural context remain comparatively neglected. Responding to this critical oversight, this article analyzes Christian-Jaque's Voyage sans espoir (1943) and Jean Grémillon's Lumière d'été from three perspectives: first, it evinces iconography in each that was central to the 1930s poetic realist films directed by figures such as Marcel Carné, Jean Renoir, and Jacques Feyder; second, it illustrates how poetic realism's characteristic focus on gender was reconfigured during the Occupation; third, it determines how these aesthetic and social aspects spoke to French society under occupation. This article ultimately argues that poetic realist praxis persisted during the war years and constituted a major vector of resistance against German rule and the Vichy government.